Dignidade humana: art. 93 da Lei 8213/1991: uma realização no acesso ao trabalho - Brasileiro, Gustavo Tambelini (2009)
This research was conceived under the perspective of many legal institutes. Despite their distinctive nature, all of them have a main tonic, the human being. Its intention is to show a person with disabilities as a pro-active individual amongst social community, being able to participate and deserving the fundamental right of labor so that he or she may glimpse at the possibility of a quantitative-qualitative insertion in the social-economical conviviality. The article 93 of act 8.213/ 1991 Act of Labor Market Reservation Quota System is examined in order to celebrate the access of people with disabilities in the market as a way of achieving the principle of human dignity. However, first the fundamental human rights are examined through a historical research, leading us to the importance of its historical evolution and its different classification, being placed in the Brazilian legal-constitutional system. In the second part of the process, the principle of human dignity is explored, from its very beginning, examining its formation as doctrinal concepts and, finally, leading to an interrelation with the fundamental human rights. This step discusses the solidification of dignity and its inseparable relation regarding fundamental rights. It also reveals a search for a new perspective related to the legal knowledge, the study of Living Law . As a third step, indications referring to labor law and its function as a social justice mechanism were made. All of these digressions are made in order to assert the importance of the human dignity principle and of the fundamental rights, especially regarding the Fundamental Labor Rights, so that, in the end, they may be seen under the perspective of people with disabilities. This is where the animus of this paper resides their access to the fundamental labor rights as a way of achieving human dignity. This project is elaborated in a way that regards the value of human beings and the legal-social institutes capable of carrying out social promotion.